2014
DOI: 10.1242/jeb.110098
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inactivation of the rickets receptor in muscle compromisesDrosophilaviability

Abstract: Bursicon is a hormone that modulates wing expansion, cuticle hardening and melanization in Drosophila melanogaster. Bursicon activity is mediated through its cognate G protein-coupled receptor (GPCR), rickets. We have developed a membrane-tethered bursicon construct that enables spatial modulation of rickets-mediated physiology in transgenic flies. Ubiquitous expression of tethered bursicon throughout development results in arrest at the pupal stage. The few organisms that eclose fail to undergo wing expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, a specific bursicon receptor was identified in D. melanogaster to be a leucinerich repeated GPCR type 2, and binding of recombinant bursicon to the receptor triggered cAMP production resulting in cuticle tanning stimulation (Luo et al, 2005). Besides, the expression of the bursiconspecific receptor was found in nervous tissues (Diao and White, 2012), epidermis (Davis et al, 2007) and muscle (Harwood et al, 2014). Similarly, the FlyAtlas database revealed that the bursicon receptor was expressed in several tissues including brain, thoracic ganglia, fat body, ovary and testis in adult D. melanogaster (Chintapalli et al, 2007).…”
Section: Reproductive Function Of P Monodon Bursiconmentioning
confidence: 99%
“…Interestingly, a specific bursicon receptor was identified in D. melanogaster to be a leucinerich repeated GPCR type 2, and binding of recombinant bursicon to the receptor triggered cAMP production resulting in cuticle tanning stimulation (Luo et al, 2005). Besides, the expression of the bursiconspecific receptor was found in nervous tissues (Diao and White, 2012), epidermis (Davis et al, 2007) and muscle (Harwood et al, 2014). Similarly, the FlyAtlas database revealed that the bursicon receptor was expressed in several tissues including brain, thoracic ganglia, fat body, ovary and testis in adult D. melanogaster (Chintapalli et al, 2007).…”
Section: Reproductive Function Of P Monodon Bursiconmentioning
confidence: 99%
“…Loss of RK function prevents cuticle sclerotization and delays the melanization of the adult fly but eventually results in a darker than normal exoskeleton Flies trans-heterozygous for loss-of-function rk mutations (rk 1 /rk 4 ) do not expand their wings, present an abnormal body shape and fail to melanize properly [9]. A comparable result was obtained when a rk RNAi or a membrane tethered bursicon hormone transgene (here called tBur), which acts as a dominant negative rk allele [16,17], was expressed in all rk-expressing cells using a rk-GAL4 driver ( Fig. 1a,b; results shown for female flies; similar results were obtained with adult male flies, Additional file 1: Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated, such modified peptide ligands exhibit enhanced effective concentration and thus provide experimental tools that facilitate the pharmacologic characterization of GPCRs. In addition, MTLs can be expressed as transgenic constructs enabling exploration of corresponding receptor function in vivo (Harwood et al, 2014). Complementing such recombinant constructs, lipidated peptides provide additional tools that can be applied in vivo to probe receptor function and validate potential therapeutic targets (Doyle et al, 2014).…”
Section: Discussionmentioning
confidence: 99%